Virtual reality psychological intervention helps reduce preoperative anxiety in patients undergoing carotid artery stenting: a single-blind randomized controlled trial - Liu, Yanhua; Wang, Rui; Zhang, Yang; Feng, Ling; Huang, Wenxia (Frontiers in Psychology, 2023)
Objective: This study aimed to explore the effectiveness and applicability of psychological intervention using Virtual Reality(VR) to reduce preoperative anxiety in patients undergoing carotid artery stenting(CAS). Methods: 124 patients 18 and 86 years scheduled for CAS were randomly divided into a VR group and a control group. The VR group patients used a VR headset to view a 16-minute Psychological Intervention Video, while the control group patients used a tablet for viewing. The primary outcome was State-Trait Anxiety Inventory (STAI), which was measured before the intervention, 20 minutes after the intervention, and 24 hours after surgery. Secondary outcomes included Patient self-efficacy, Sleep quality, satisfaction, and VR Applicability. Results: The 2 groups were similar in terms of demographic information and preoperative STAI scores and preoperative self-efficacy scores. The VR group had lower S-AI scores than the control group both after the intervention and after surgery. The postoperative self-efficacy was higher in the VR group than in the control group. Sleep monitoring showed no significant differences of the two groups in post-intervention sleep quality. As for satisfaction, the VR group scored higher in all aspects except scheduling. In addition, 47 (85.45%) of the patients used VR reported comfortable experience and only 5 (9.09%) encountered mild adverse effects. Conclusion: The use of VR preoperative psychological interventions is beneficial in reducing preoperative anxiety in CAS and improving the efficacy of patients' chronic disease self-management. With the development of VR devices, which demonstrate better comfort and safety, more comprehensive and in-depth studies are worthwhile in the future.